Negative Home Equity and Household Labor Supply - BERNSTEIN, ASAF (Journal of Finance, 2021)
ABSTRACT Using U.S. household‐level data and plausibly exogenous variation in the location‐timing of home purchases with a single lender, I find that negative home equity causes a 2% to 6% reduction in household labor supply. Supporting causality, households are observationally equivalent at origination and equally sensitive to local housing shocks that do not cause negative equity. Results also hold comparing purchases within the same year‐metropolitan statistical area that differ by only a few months. Though multiple channels are likely at work, evidence of nonlinear effects is broadly consistent with costs associated with housing lock and financial distress.